Academic entrepreneurship university spinoffs and wealth creation - Shane, Scott Andrew 1964- (Edward Elgar, 2004)
In this unique and timely volume, Scott Shane systematically explains the formation of university spinoff companies and their role in the commercialization of university technology and wealth creation in the United States and elsewhere. The importance of university spinoff activity is discussed and the historical development of university spinoff ventures is traced over time
Includes bibliographical references and index
Keywords: Spin-off-Unternehmensgründung; Forschungskooperation; Akademiker; Spitzentechnologie; Unternehmer; Management; Wissenschaftstransfer; Technologietransfer; Unternehmensgründung; Hochschule; Industrieforschung; USA; Entrepreneurship / United States; Technology transfer / United States; High technology industries / United States; Academic-industrial collaboration / United States; University-based new business enterprises / United States; Research, Industrial / United States